2018
DOI: 10.3126/jnhrc.v16i2.20302
|View full text |Cite
|
Sign up to set email alerts
|

Work-related Injury among Welders Working in Metal Workshops of Dharan Municipality, Nepal

Abstract: Background: Injuries are a problem worldwide in all occupations. Welders are exposed to many hazards at work resulting in a variety of health problems including injuries at work. This study was conducted to find out the prevalence and factors associated with injuries among welders in Dharan city of eastern Nepal.Methods: A cross sectional study was conducted among 86 welders in Dharan city. Occurrence of injury in past 2 weeks and past 12 months were recorded. Data regarding sociodemographic along with occupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(25 reference statements)
2
3
0
Order By: Relevance
“…Welders who did not use eye PPE while working were almost twice at risk of eye injuries. This is consistent with similar studies in Nigeria [ 3 ] and Nepal [ 31 ] where it was reported that nonuse of eye PPE was significantly associated with eye injuries. The primary purpose of any personal protective equipment is to protect the user against health or safety risks at work.…”
Section: Discussionsupporting
confidence: 93%
“…Welders who did not use eye PPE while working were almost twice at risk of eye injuries. This is consistent with similar studies in Nigeria [ 3 ] and Nepal [ 31 ] where it was reported that nonuse of eye PPE was significantly associated with eye injuries. The primary purpose of any personal protective equipment is to protect the user against health or safety risks at work.…”
Section: Discussionsupporting
confidence: 93%
“…The current study recorded a significant association between non-use of protective ocular devices and having occupation ocular injuries. Similar findings were recorded in studies in Nigeria [4], Ghana [17], and Nepal [31]. This means that sawmill workers who do not use any protective eye device are exposing themselves to ocular hazards.…”
Section: Factors Associated With Occupational Ocular Hazardssupporting
confidence: 88%
“…15 This finding is consistent with those found in similar studies conducted in Nepal and India where welders were predominantly male under the age of 25 years. [16][17][18][19] The overall prevalence of occupational injuries among welders working in small scale metal workshops was high at 87.8%. These findings are consistent with those found by other similar studies conducted in South India, Nigeria and Kenya.…”
Section: Data Collectionmentioning
confidence: 99%